Fundamentals of Human Communication Social Science in Everyday Life - DeFleur, Melvin L. (Melvin Lawrence); Patricia Kearney; Timothy G. Plax; Melvin L. DeFleur (New York The McGraw-Hill, 2013)
This theory-based introduction to basic concepts in human communication provides coverage of new and innovative theories as well as the more traditional coverage of an introduction to communication course, giving students an understanding of the discipline and helping them develop strategies for becoming better communicators.
Keywords: Communication